Effect of Different Diameter on Performance of Air-conditioning Umbrella with Semiconductor Refrigeration - He Lijuan; Wu Xinwei; Wang Di; Dong Jinzhong; Jin Guang (Zhileng xuebao)
Aiming at the problem of large volume and difficulty in the maintenance of compression-type air-conditioning umbrellas, an air-conditioning umbrella with semiconductor refrigeration is introduced. A test bench was built to measure the temperature and flow field in the umbrellas with different diameters ( 36 cm, 38 cm, and 40 cm). Based on the Peltier effect and the structural characteristics of the air conditioning umbrella, the lower air supply mode was applied within the air-conditioning umbrella with semiconductor refrigeration. Experimental results indicate that the air speed in the umbrella with a diameter of 38 cm is between 0.23 m/s and 0.47 m/s, and the maximum temperature difference between air-conditioned area and ambient environment is 3.04 ℃, which can thus create a comfortable local environment.